Students' Perception of Syiah Kuala University History Education Against Online Lectures as a Learning Tool During the COVID-19 Pandemic - Amalya Krisna Waty (Riwayat: Educational Journal of History and Humanities, 2022)
This study aims to determine the perception of historical education students at Syiah Kuala University (USK) towards online learning in terms of several indicators, namely learning materials and evaluation questions, community, online lecturers, collaboration opportunities, and multimedia. The approach used in this research is a qualitative approach with the type of phenomenological research. The subjects of this research were USK history education students batch 2018. Data collection was carried out by interview. Data analysis techniques with data reduction, data presentation, and drawing conclusions. The results showed that the materials and evaluation questions were available and could be downloaded by students. Have a community to learn and discuss together. Students are more inclined to video conference-based media in the implementation of online learning, namely Google Meet with Google Classroom as a forum for collecting assignments. The use of media has not been maximized.